BENZERLiK VE FARKLILIKLAR EKSENiNDE ALEViBEKTAŞi iNANÇLARI ÜZERiNE BiR DEGERLENDiRME - Azar, Birol (Fırat University, 2005)
The issue of whether Alevism and Bektashism are religions independent from Islam or they are tariqats/sects connected to Islam, has always been an argument among both theorists and those who are interested in this subject. Turks have reflected a lot of components from their former believes to preseni religious lives in Iradition because of both their characteristics and their lslamization process's being long and fluctuative. In Alevi-Bektashi beliefihis situation seems to be more visi.ble. The most important problem which is encountered by researchers who make investigations upon the issue of Alevism and Bektashism, is the matter of getting these t:wo terms mixed up and/or using one ofthem in the name of the other.
Keywords: Religious Studies; Din Araştırmaları